Mononormativity and Related Normative Bias in the UK Immigration System: The Experience of LGBTIQ+ Asylum Seekers - Gordon-Orr, Rose (Frontiers in Human Dynamics, 2021)
This article examines the impact that different normative understandings of sexuality and relationships have on LGBTIQ+ people's experience of the UK Immigration System, with a particular focus on mononormative conceptions that privilege forms of coupledom. By examining legal regulations and case judgments, the mononormative bias is shown to disadvantage LGBTIQ+ asylum seekers and make it difficult for those not seen to be in long-term romantic relationships to have their sexuality acknowledged and their claims for asylum upheld. The article considers how mononormativity intersects with heteronormative stereotypes and narrow homonormative prescriptions of gay identity such as “coming out” or expressing particular lifestyle choices. Taken together these normativities combine in a culture of disbelief in the immigration system that negates the self-identification of LGBTIQ+ asylum seekers and refugees by requiring them to conform to norms that do not reflect the diversity of queer lives and experiences.